Halk İnanışlarında ve Ritüellerinde Kaotik Çocuk İmgesi - SERDAR, GÜRÇAY; Duran, Alev (Uluslararası Kıbrıs Üniversitesi, CIU, 2025)
The concept of childhood is a multifaceted one, both cross-culturally and within national cultures. Perspectives associated with this concept have varied across historical processes and different geographical regions. In the past, children were often perceived as anonymous, uncategorized beings, frequently considered equivalent to adults. However, in contemporary societies, children are viewed as valuable individuals, nurtured and educated with care as the adults of the future, with all available resources used to meet their needs to the fullest extent. The subject and aim of our study, which evaluates data obtained through qualitative research and document analysis, is to explore the image of the child that emerges in folk beliefs, narratives, and rituals from a broad perspective. To achieve this, a comparative approach has been adopted, examining the depiction of children from the past to the present and in comparison with Western societies. In order to make this distinction, the image of the child has been analyzed as a recurring and varied motif in folk narratives, such as the Dede Korkut Kitab & imath;, which reflects the Turkish identity of the Middle Ages, and the Alevi-Bektashi velayetname (hagiographies), which provide a realistic portrayal of the traditional perspective. Doubtlessly, although a wide range of sources can be consulted to critically examine the image of the child, for the specific objectives of this study, two primary sources have been selected to facilitate a historical analysis. In our study, after the introduction, definitions and evaluations regarding the chaotic image of the child are provided. Then, the perspectives of societies, considered traditional, towards this image are examined, and the place and significance of the child image in transition rituals such as birth, circumcision, marriage, and death are deepened with examples.Later, the role and status of the child encountered in oral folk narratives, which are records of popular beliefs and rituals, are examined in detail. Understanding the changes in the concept of childhood throughout history and their effects on this concept is considered crucial for the future of societies. In this context, we believe that harmonizing tradition with globalization will positively contribute to the construction of society's future.
The Image of the "Chaotic Child" in Folk Beliefs and Rituals
Keywords: Child; Ritual; Folk Belief; Image; Chaotic